Review on interlamellar spacing and spheroidization rate for hypoeutectoid steel and hypereutectoid steel - Arjun Dev Pandey. (2009)
This Final Year Project shows how the rate of spheroidization is dependent on the thickness of the pearlite layers or lamellar. When pearlite microstructure is subjected to an appropriate temperature for a prolong period of time, spheroidization occurs. The pearlite structure breaks down into cementite globules or coalesces into spheroids in a ferrite matrix. This project was carried out on hypoeutectoid steel and hypereutectoid steel over varying duration of heat treatment time.